Meeting report of the 6th Heidelberg Myeloma Workshop: current status and developments in diagnosis and therapy of multiple myeloma - Merz, Maximilian; Raab, Marc-Steffen; Goldschmidt, Hartmut; Hillengaß, Jens (Journal of cancer research and clinical oncology, 2017)
PurposeThe 6th Heidelberg Myeloma Workshop was held on May 5th and 6th, 2017 in the lecture hall of the University Hospital Heidelberg.Methods and resultsMain topics of the meeting were (1) biology and genomics of multiple myeloma, (2) diagnostics and prognostic factors, (3) role of immunotherapy in multiple myeloma, as well as (4) therapy of multiple myeloma—drugs and treatment strategies.ConclusionThe landscape for the treatment of newly diagnosed and relapsed disease has significantly changed since the last Heidelberg Myeloma Workshop in 2015. Updates on the current developments were presented at the meeting.